Crowdfunding und Plattformregulierung Grundzüge des europäischen Rechts für Schwarmfinanzierungsdienstleistungen - Linardatos, Dimitrios (Recht und Digitalisierung | Digitization and the Law, 2023)
To establish a Capital Markets Union that improves the access to financing for innovative, non-listed companies, the European legislator has harmonized the law on platform-based project financing (Crowdfunding) to a large extent. The adopted Crowdfunding Regulation entails for Crowdfunding Service Providers far-reaching and, in particular, novel duties of conduct, organization, information as well as gatekeeper requirements. Thereby, the operators of Crowdfunding Platforms are facing considerable legal as well as factual challenges. This book offers valuable orientation by providing a systematic overview of the key points of the European legal requirements.